Penggunaan Obat Terlarang dalam Medis: Perspektif Hukum Positif dan Hukum Islam - Nurul Raudatul Auliah; Beatrice Mauren Delicia; Bunga Nirvana; Firdha Apriliana Zahra; Ayuk Pebriyani; Baidhowi (PT. Hasba Edukasi Mandiri, 2025)
This study examines the use of narcotics in the medical field from the perspective of Indonesian positive law and Islamic law. Narcotics have the potential to cause dependence and abuse, but they also have therapeutic benefits such as reducing pain and assisting in the anesthesia process. In Indonesian positive law, regulations regarding narcotics are contained in Law Number 35 of 2009, which allows their use for medical and research purposes under government supervision. Meanwhile, in Islamic law, narcotics are classified as intoxicating substances that are forbidden to use, except in emergency conditions when no other halal drugs are available. This study uses a normative juridical method with a literature study approach through a literature review of legislation, legal literature, the Qur'an, and Hadith. The results of the study show that both legal systems have similar views, namely allowing the limited use of narcotics for humanitarian purposes with strict supervision and legal responsibility.